(untitled) (Damascus University Journal of arts and humanities sciences, 2024)
Plato built his aesthetic philosophy on an ontological basis. He formulated the most coherent aesthetic theories and created degrees of beauty. The first is physical beauty and placed it at the bottom of the pyramid of beauty, then followed by the beauty of morals and the soul, and then absolute beauty at the top of the pyramid. Since love is considered a form of beauty, it formed a basic tone in most of Plato’s writings. Plato considered that the obsession with love that connects the truth in the philosopher is the best kind of divine obsession, through which this world can be perceived with its material and helps the soul to remember the spiritual world in which it was before its fall to the earth. Plato’s theory of love was so comprehensive that it became a basis for philosophy from antiquity to the Middle Ages. It claims that external things are the origin on which knowledge depends, but it is not material, sensible things, but transcendental ideals.Therefore, ideal love is much higher than physical love, and Plato emphasized the dialectic between love and beauty, both of which can only be achieved by the return of the soul to the world of ideals, and by reaching the ideal aesthetic level of man, he will have reached the subject of love, which tends to beauty. And the relationship of the ideal of beauty is strong with the ideal of goodness according to Plato. Access to the ideal of good is linked to reaching the ideal of beauty, and a person does not feel beauty until after he has achieved a lot of good.